Utilização de farelo do mesocarpo de babaçu em substituição ao grão de milheto na terminação de bovinos e a influência na maciez da carne - Souza, Maria Izabel Amaral (2014)
Due to the need for alternative sources of food for cattle nutrition, research on agribusiness by-products has been carried out, such as the use of babassu mesocarp bran ( MB ) in the ruminants diet. In this experiment, we analyzed 30 Longissimus dorsi samples obtained from animals that received babassu meal replacing pearl millet grain, in six different treatments: ( T1 ) 100% pearl millet ; ( T2 ) 88% pearl millet + 12% MB; ( T3 ) 76% pearl millet + 24% MB, ( T4 ) 64% pearl millet + 36% MB, ( T5 ) 52% pearl millet and 48% MB, and ( T6 ) 100% corn. Several physico-chemical analyzes were performed to identify possible factors affecting the tenderness of the meat. We use flame atomic absorption spectrophotometry, to quantify the minerals: copper, iron, calcium, magnesium, manganese, zinc, sodium and potassium from babassu mesocarp bran, pearl millet and Longissimus dorsi samples. In babassu mesocarp bran the minerals that presented the greatest levels were K ( 590.49 mg/100 g ), followed by Ca, Fe, and Mg, in pearl millet K ( 484.86 mg/100 g ) followed by Mg and Capresented the highest level, whithout showing concentrations of Fe, in meat samples Mn was not found with the methodology used, and the minerals with the highest concentrations were K, (with difference between the standard treatment and the one with greater MB inclusion), followed by Na and Mg. The average shear force was 5.74 kgf. The water holding capacity was determined by thawing weight loss ( 13%), cooking weight loss (14.16%) and pressure weight loss (26.3%) . Regarding the myofibrillar fragmentation index (MFI) there was difference between the standard treatment and the one with greater MB inclusion, demonstrating that the MB can reduce the MFI. As for total collagen, the value found was 3.06% and soluble collagen was of 7.5% ( relative to total collagen content). The MB is an interesting alternative source for ruminants' feed and, taking MFI into consideration, the concentrations lower than 48% MB would be ideal, MB inclusion also favours potassium concentration.